KAJIAN NILAI PADA TOPONIMI DI WILAYAH KOTA CIREBON SEBAGAI POTENSI SUMBER BELAJAR GEOGRAFI - Segara, Nuansa Bayu (Jurnal Geografi, 2017)
Naming the place is part of human culture that can not be separated. The impression of a place for the human is so profound that the naming of a place often has values that need to be preserved its existence. Recently, naming the place in the city of Cirebon not see elements of local value. Settlement development, housing and entertainment venues far from the local values that should be safeguarded. The names of the residential complex are no longer using local rules especially involve local figures for naming the place. This research aims to inventory the existing local value on toponymy. After conducting a qualitative study with phenomenology, resulting in that the pattern of naming place at the study site in District Kesambi and Harjamukti motivated by, geographic elements, biological element, folklore, socio-historic and prominent. Background naming places that have been identified in fact have values that potentially serve as a source of learning in teaching geography or social studies in school.